University 4.0 concept: educational and scientific policies, innovative development of vocational education and training - Chernaya, Irina P.; Masyuk, Natalya N.; Prosalova, Veronika S.; Bodunkova, Anna G.; Bushueva, Marina A. (Frontiers in Education, 2023)
The paper aims to generalize theoretical and practical aspects of educational and scientific policies and management of the vocational education innovative development within a University 4.0 model. The study of the University 4.0 continuum in this paper is based on a systematic approach. Our research content and construct validity, and reliability of its results were analyzed at the stage of developing a University 4.0 scale of environments using the SPSS (Statistical Package for the Social Sciences) and LISREL (Linear Structural Relations) software packages. Based on an explanatory factor analysis we developed a three-dimensional indicative scale of environments for an innovative entrepreneurial university. The efficient and reliable tool which is offered for assessing the internal environments of an innovative entrepreneurial university and its activities as a University 4.0 type is scaling. By scaling the University 4.0 environments our universities could succeed in upgrading their innovative entrepreneurial characteristics aimed to benefit their students, government agencies, and the entire economy at the macro level.